Pengaruh Psychological Capital Terhadap Work Engagement Karyawan Internasional Komputer - Luluk Hidayah, Nova; Miftahul Khairi, Alfin (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2026)
This study aims to examine the impact of Psychological Capital on Work Engagement among employees of Internasional Komputer. The hypothesis proposed in this study states that the level of employees’ Work Engagement at Internasional Komputer is significantly influenced by Psychological Capital. The method employed is a quantitative approach with a descriptive analytical framework. The study involved all 50 employees of Internasional Komputer as the research sample. This research utilized simple linear regression for data analysis. The instruments used included the Psychological Capital scale, consisting of 23 items, and the Work Engagement scale, consisting of 17 items. Both instruments were tested for reliability, yielding a Cronbach’s alpha coefficient of 0.887 for the Psychological Capital and Work Engagement scales. The results of the analysis indicate that 57.9% of the variance in Work Engagement is explained by Psychological Capital, as evidenced by an R-squared value of 0.579, while the remaining 42.1% is influenced by other factors not examined in this study. Furthermore, the significance value of 0.000, which is less than 0.05 in the simple regression analysis, indicates that the level of employees’ Work Engagement at Internasional Komputer is significantly affected by Psychological Capital. Keywords: Work Engagement; Employees; Psychological Capital.